1984
DOI: 10.1055/s-2008-1053735
|View full text |Cite
|
Sign up to set email alerts
|

Persistent hydrocephalus following removal of choroid plexus papilloma of the lateral ventricle

Abstract: We report a case of choroid plexus papilloma of the left lateral ventricle, which illustrates the difficulties of diagnosis of these tumours with air studies in advanced hydrocephalus. The hydrocephalus was apparent at the age of three months, but ventriculography failed to reveal the true nature of the communicating hydrocephalus. A ventriculocaval shunt was inserted, but the hydrocephalus progressed, in spite of the fact that the shunt was functioning well. The diagnosis of a papilloma of the choroid plexus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
(2 reference statements)
0
6
0
3
Order By: Relevance
“…53 It is has been observed that hydrocephalus can persist even after successful excision of the choroid plexus. 26,40,47,51 In this series, nine children required ventricular shunts several months after tumor removal. Similar findings have been reported in other series as well.…”
Section: Pathophysiological Characteristics Of Hydrocephalusmentioning
confidence: 89%
See 1 more Smart Citation
“…53 It is has been observed that hydrocephalus can persist even after successful excision of the choroid plexus. 26,40,47,51 In this series, nine children required ventricular shunts several months after tumor removal. Similar findings have been reported in other series as well.…”
Section: Pathophysiological Characteristics Of Hydrocephalusmentioning
confidence: 89%
“…2 In children, tumors of the choroid plexus are located most often in the lateral ventricle, but they can also be found in the third ventricle and in the posterior fossa. 6,8,10,11,13,20,21,27,29,42,56,60 Of particular surgical interest in cases of choroid plexus tumors are the associated hydrocephalus, its pathophysiological characteristics, and the way it interferes with removal of the tumor; 15,17,22,26,30,37,40,50,53,57,59 and the increased vascularity of these tumors, which makes surgery challenging, particularly in cases of carcinoma because the patients tend to be of young age. 7,24,41,47,51,54,58,62 Although papillomas are usually cured by surgery, carcinomas have a tendency to recur.…”
mentioning
confidence: 99%
“…Tamburrini et al (2006) have shown that, even after a choroid plexus resection, the CSF drains at the rate of 1000 ml/day. The progression of hydrocephalus after a complete resection of the tumorous tissue has also been observed, so a shunt had to be placed inside both ventricles, even 3 years after the surgery (Husag et al, 1984). In 9 out of 33 children (Pencalet et al, 1998), a ventriculoperitoneal shunt was required after tumor excision, which questions the notion that cerebrospinal fluid oversecretion is the only cause of hydrocephalus.…”
Section: Criticism Of the Classic Hypothesis Of Cerebrospinal Fluid Fmentioning
confidence: 99%
“…Existem relatos esporádicos de crianças com esta patologia e sem hidrocefalia 21,22 . Desde estudos de Russell, em 1941, a fisiopatologia da hidrocefalia que acompanha estes tumores tem sido discutida e parece que múltiplos fatores podem ser responsabilizados, tais como a hiperprodução do líquor pelo tumor [23][24][25] , a obstrução do fluxo liquórico pelo próprio tumor (obstrução do forame de Monro, terceiro ou quarto ventrículo) ou a dificuldade na reabsorção devido a fibrose como consequência de repetidas hemorragias ou mesmo descamação tumoral 25 . Vários estudos defendem as duas teorias.…”
Section: Tabela 1 Relação Dos Pacientes Com Tumores Do Plexo Coróideounclassified
“…A hiperprodução de líquor é constatada através da observação de que, em alguns casos, a hidrocefalia desaparece após a cirurgia com retirada total da lesão 4,14,[26][27][28] . Outros autores 3,6,25,28,29 citam casos em que, apesar da retirada do tumor, persistiu a hidrocefalia. Interessante é que existem divergências quanto ao uso de derivações: Matson e Crofton 4 , em 1960, afirmavam que existiam fortes evidências de que a hidrocefalia era causada unicamente pela hiperprodução de líquor pelo tumor e a afirmativa se baseava no fato de que em todas as crianças em que um papiloma do plexo coróideo do ventrículo lateral foi extirpado totalmente, não se fez necessário o uso de derivações; Raimondi e Gutierrez 6 , em 1976, relatam da necessidade de derivações ventriculares definitivas em 16 (69,5%) das 23 crianças submetidas a retirada do tumor do plexo coróideo e Lena e col. 3 em 1990 relatam que 17 (70,8%) das 24 crianças submetidas a ressecção de tumor do plexo coróideo necessitaram de derivação liquórica permanente.…”
Section: Tabela 1 Relação Dos Pacientes Com Tumores Do Plexo Coróideounclassified